Augmenting ideational fluency in a creativity task across multiple transcranial direct current stimulation montages - Evangelia G. Chrysikou (Nature Portfolio, 2021)
Abstract Neuroimaging and transcranial direct current stimulation (tDCS) research has revealed that generating novel ideas is associated with both reductions and increases in prefrontal cortex (PFC) activity, and engagement of posterior occipital cortex, among other regions. However, there is substantial variability in the robustness of these tDCS‐induced effects due to heterogeneous sample sizes, different creativity measures, and methodological diversity in the application of tDCS across laboratories. To address these shortcomings, we used twelve different montages within a standardized tDCS protocol to investigate how altering activity in frontotemporal and occipital cortex impacts creative thinking. Across four experiments, 246 participants generated either the common or an uncommon use for 60 object pictures while undergoing tDCS. Participants also completed a control short-term memory task. We applied active tDCS for 20 min at 1.5 mA through two 5 cm × 5 cm electrodes over left or right ventrolateral prefrontal (areas F7, F8) or occipital (areas O1, O2) cortex, concurrent bilateral stimulation of these regions across polarities, or sham stimulation. Cathodal stimulation of the left, but not right, ventrolateral PFC improved fluency in creative idea generation, but had no effects on originality, as approximated by measures of semantic distance. No effects were obtained for the control tasks. Concurrent bilateral stimulation of the ventrolateral PFC regardless of polarity direction, and excitatory stimulation of occipital cortex did not alter task performance. Highlighting the importance of cross-experimental methodological consistency, these results extend our past findings and contribute to our understanding of the role of left PFC in creative thinking.